Bank Privatization in Sub-Saharan Africa: The Case of Uganda Commercial Bank - Clarke, George R. G.; Cull, Robert; Fuchs, Michael (2012)
Because large state-owned banks are often the only financial service providers in remote areas of low-income countries, policymakers worry that even if privatization improves performance, it might reduce access. We study this issue through a case study: the privatization of Uganda Commercial Bank (UCB) to the South African bank Stanbic. Though market segmentation remains a concern since Stanbic faces little or no direct competition in many remote areas, some innovative aspects of the sales agreement have enabled the bank to improve its profitability while maintaining, or even improving, access to financial services for some hard-to-serve groups.